Comparative proteomic analysis of the response to silver ions and yeast extract in Salvia miltiorrhiza hairy root cultures - Wang, Yajun (Plant physiology and biochemistry : PPB, 2016)
Copyright © 2016 Elsevier Masson SAS. All rights reserved.